(untitled) (Revista Iberoamericana de Bioética, 2017)
The use of the term vulnerability in the discussion of bioethics, either as a concept or as a reality, has become increasingly recurrent. The first, and also most important use of this term is to protect subjects participating in experiments, but its use has been expanded to other situations. The aim of this research was to identify the subjects or realities that are classified as vulnerable. We used the descriptors “bioethics” and “vulnerability” to search for literature in Scielo.BR, Scielo.ORG and Lilacs, and analyzed 79 articles. Furthermore, in these articles we identified four categories of vulnerability that can be grouped as vulnerability in: [1] stages of life and gender; [2] health, disease and research; [3] socioeconomic and cultural exclusion; [4] and environment. This categorization demonstrates that the bioethical reflection on the vulnerability of life is still predominantly anthropocentric, which makes the protection of the dignity of life as a whole a challenge that is still to be faced by bioethical discussion.